2010
DOI: 10.1111/j.1600-0625.2009.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Nestin and SOX9 and SOX10 transcription factors are coexpressed in melanoma

Abstract: Nestin is an intermediate filament expressed in proliferating neural progenitor cells and has been considered as a stem cell marker. Nestin is also found in melanoma and we recently demonstrated that its expression in melanoma cell lines is regulated by the transcription factors SOX9 and SOX10, but not BRN2. In this study, the expression levels of nestin, BRN2, SOX9 and SOX10 were analysed in tissues of melanoma (n = 78) and melanocytic nevi (n = 26) by immunohistochemistry. All proteins were highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 31 publications
(41 reference statements)
9
60
2
Order By: Relevance
“…Besides morphological and histopathological markers, several molecular markers have diagnostic and prognostic utility (1). These include markers on the melanoma, for example methylthioadenosine phosphorylase (MTAP) (2), nestin and SOX9 (3), and markers in patients' blood, for example p-proteasome levels (4). The search for a prognostic marker continues, however.…”
Section: Introductionmentioning
confidence: 99%
“…Besides morphological and histopathological markers, several molecular markers have diagnostic and prognostic utility (1). These include markers on the melanoma, for example methylthioadenosine phosphorylase (MTAP) (2), nestin and SOX9 (3), and markers in patients' blood, for example p-proteasome levels (4). The search for a prognostic marker continues, however.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have demonstrated that the neural stem/progenitor cell marker nestin, a type VI intermediate filament transiently expressed in early migrating and proliferating neuroectodermal cells, 18 is expressed in primary and metastatic melanomas. [19][20][21][22][23] Furthermore, this expression seem to correlate with more advanced disease and decreased 5-year survival. 24,25 In contrast, the majority of melanocytic nevi, even dysplastic nevi, showed no or weak nestin staining.…”
mentioning
confidence: 99%
“…Nestin was also co-expressed with SOX9 and SOX10, which may contribute to its transcriptional up-regulation, in primary and secondary melanoma specimens and associated with a poor survival of melanoma patients [98][99][100][101] . The analyses by flow cytometry and quantitative reverse transcription-PCR (qRT-PCR) of the expression level of nestin performed on 23 tissue specimens from patients with stage Ⅲ-Ⅳ melanoma has also indicated that this stem cell-like marker was expressed at a higher level in stage Ⅳ patients compared to stage Ⅲ /Ⅳ with no evidence of disease [93] .…”
Section: Potential Biomarkers In Melanoma Stem/progenitor Cellsmentioning
confidence: 99%
“…The immunohistochemical analysis of nestin, which is a neuroepithelial intermediate filament expressed in proliferative neuroectodermal progenitor cells during embryonic development and adult bulge areas-resident stem cells in hair follicle, has also indicated that its expression was significantly enhanced in primary and metastatic melanoma tissue specimens as compared to benign and normal melanocytes [96][97][98][99][100][101] . Nestin was also co-expressed with SOX9 and SOX10, which may contribute to its transcriptional up-regulation, in primary and secondary melanoma specimens and associated with a poor survival of melanoma patients [98][99][100][101] .…”
Section: Potential Biomarkers In Melanoma Stem/progenitor Cellsmentioning
confidence: 99%